Health systems, mechanisms of governance and governmental porosity in comparative perspective - Ribeiro, José Mendes (2022)
This article presents a comparative analysis of 10 selected countries about stablished relations of participative governance, socioeconomic profiles and health care systems with health outcomes and World Governance Indicators. Major sources were databases produced and/or compiled by World Bank. Analytical model adopts institutionalist approach to deal with social protection and participative governance. Participative governance, as used, recovers notions of societal participation, government porosity and responsive regulation. Outcomes show a solid convergence of more distributive socioeconomic profiles, heath systems more universalist and with higher government financing and better governance indicators. This analysis supports arguments that socially virtuous institutional paths subjected to positive feedback favors better social and political outcomes along time.